The Infectious Basis of ACPA-Positive Rheumatoid Arthritis - Sakkas, Lazaros I.; Daoussis, Dimitrios; Liossis, Stamatis-Nick; Bogdanos, Dimitrios P. (Frontiers in Microbiology, 2017)
Rheumatoid arthritis (RA) is associated with HLA-DRB1 shared epitope (HLA-DRB1SE) and anti-citrullinated protein autoantibodies (ACPAs). ACPAs precedes the onset of clinical and subclinical RA. There are strong data for three infectious agents as autoimmunity triggers in RA, namely Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans causes of periodontal disease (PD), and Epstein-Barr virus (EBV). P. gingivalis expresses arginine gingipains, that cleave proteins at the arginine residues, and peptidyl arginine deiminase (PPAD), which citrullinates arginine residues of proteins, thus forming neoantigens that lead to ACPA production. Peripheral blood plasmablasts from ACPA+RA patients produce ACPAs the majority of which react against P. gingivalis. A. actinocycetemcomitans produces leukotoxin A, a toxin that forms pores in the neutrophil membranes and leads to citrullination and release of citrullinated autoantigens in the gums. EBV can infect B cells and epithelial cells and resides as latent infection in resting B cells. Abs against citrullinated peptides derived from EBV nuclear antigen appear years before RA and cross-react with human citrullinated fibrin. Citrullinated proteins are potential arthritogenic autoantigens in RA. The conversion of arginine to citrulline increases the peptide binding affinity to HLA-DRB1SE. Also, citrullinated fibrinogen induces arthritis in HLA-DRB1*0401 transgenic mice, and transfer of their splenic T cells causes arthritis to recipient mice.